Directional preference may enhance hunting accuracy in foraging foxes - Červený, Jaroslav; Begall, Sabine; Koubek, Petr; Nováková, Petra; Burda, Hynek (Biology letters, 2011)
Red foxes hunting small animals show a specific behaviour known as 'mousing'. The fox jumps high, so that it surprises its prey from above. Hearing seems to be the primary sense for precise prey location in high vegetation or under snow where it cannot be detected with visual cues. A fox preparing for the jump displays a high degree of auditory attention. Foxes on the prowl tend to direct their jumps in a roughly north-eastern compass direction. When foxes are hunting in high vegetation and under snow cover, successful attacks are tightly clustered to the north, while attacks in other directions are largely unsuccessful. The direction of attacks was independent of time of day, season of the year, cloud cover and wind direction. We suggest that this directional preference represents a case of magnetic alignment and enhances the precision of hunting attacks.
Keywords: predátorské chování; Česká republika; ekosystém; Czech Republic; Predatory Behavior; Animals; magnetismus; Magnetics; lišky; Ecosystem; zvířata; Foxes